Teaching with educational technology in the 21st century the case of the Asia Pacific region - Inoue, Yukiko; Bell, Suzanne (Information Science Publ., 2006)
"This book explores how education is no longer confined to a geographical space and reaches out as a model to all interested in promoting quality higher education across geographical and cultural borders"--Provided by publisher.
"This book explores how education is no longer confined to a geographical space and reaches out as a model to all interested in promoting quality higher education across geographical and cultural borders"--Provided by publisher
Includes bibliographical references and index
Keywords: Enseignement supérieur - Asie; Enseignement supérieur - Pacifique, Région du; Nouvelles technologies de l'information et de la communication en éducation; Technologie éducative - Asie; Technologie éducative - Pacifique, Région du; Education, Higher -- Asia; Education, Higher -- Pacific Area; Educational technology -- Asia; Educational technology -- Pacific Area; Informationstechnik; Hochschule; Asien; Pazifischer Raum; Asiatisch-Pazifischer Raum